A New Approach of 3D Lightning Location Based on Pearson Correlation Combined with Empirical Mode Decomposition - Yanhui Wang; Yingchang Min; Yali Liu; Guo Zhao (Remote Sensing, 2021)
To improve the accuracy of pulse matching and the mapping quality of lightning discharges, the Pearson correlation method combined with empirical mode decomposition (EMD) is introduced for discharge electric field pulse matching. This paper uses the new method to locate the lightning channels of an intra-cloud (IC) lightning flash and a cloud-to-ground (CG) lightning flash and analyzes the location results for the two lightning flashes. The results show that this method has a good performance in lightning location. Compared with the pulse-peak feature matching method, the positioning results of the new method are significantly improved, which is mainly due to the much larger number of positioning points (matched pulses). The number of located radiation sources has increased by nearly a factor of seven, which can significantly improve the continuity of the lightning channel and clearly distinguish the developmental characteristics. In the CG flash, there were three negative recoil streamers in the positive leader channel. After the three negative recoil streamers were finished, taking approximately 1 ms, 12 ms, and 2 ms, respectively, the negative leader channel underwent a K-process. The three negative recoil streamers are not connected to the K-processes in the negative leader channel. We think that the three negative recoil streamers may have triggered the three K-processes, respectively.